2006
DOI: 10.1124/jpet.106.112912
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Metallothionein by Manganese Is Completely Dependent on Interleukin-6 Production

Abstract: Metallothionein (MT) is a cysteine-rich protein that binds to and is inducible by heavy metals such as cadmium and zinc. However, the precise mechanism of MT induction by other metals remains unclear. In the present study, we investigated the mechanism of MT induction by manganese, focusing on the involvement of cytokine production. Administration of MnCl 2 to mice resulted in the induction of MT dose-dependently in the liver with little accumulation of manganese. Speciation analysis of metals in the liver cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
0
36
1
Order By: Relevance
“…The oxidative stability of yolk lipids was not significantly different during whole time of storage (40 days) in both groups of birds fed diets enriched with manganese from organic sources. One of the most important functions of Mn is related to its antioxidative effect mediated by Mn-superoxide dismutase, or by increasing the synthesis of metallothionein (Kobayashi et al, 2007), which can reduce oxidative damage caused by free radicals. The suppression of lipid oxidation in egg yolk from hens supplemented with organic Mn sources may be explained by this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stability of yolk lipids was not significantly different during whole time of storage (40 days) in both groups of birds fed diets enriched with manganese from organic sources. One of the most important functions of Mn is related to its antioxidative effect mediated by Mn-superoxide dismutase, or by increasing the synthesis of metallothionein (Kobayashi et al, 2007), which can reduce oxidative damage caused by free radicals. The suppression of lipid oxidation in egg yolk from hens supplemented with organic Mn sources may be explained by this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic cytosol fractions of Cd-injected mice were analyzed by HPLC-ICP/MS. The column (TSK gel G3000SW) used in this analysis can separate the two major MT isoforms (MT-1 and MT-2) in a single elution (Kobayashi et al, 2007). As shown in Fig.…”
Section: No Differences In Accumulation and Distribution Of CD In Thementioning
confidence: 99%
“…Supernatants were assayed for reduced-form of GSH using GSSG/GSH Quantification Kit (Dojindo Laboratories, Kumamoto, Japan) according to the manufacture's instruction. The hepatic MT protein levels were determined by Hgbinding assay (Kobayashi et al, 2007). Mercury bound to MT was measured using a mercury analyzer RA-2A (Nippon Instruments, Tokyo, Japan).…”
Section: Gsh and Mt Levelsmentioning
confidence: 99%
“…Recently, we have demonstrated that interleukin-6 (IL-6) produced by various metal compounds such as Mn, cerium (Ce) and vanadium (V) plays an important role in the induction of MT in the liver. [6][7][8] However, little information is available concerning MT induction by Pb compounds. An early study in 1980s showed that intraperitoneal administration of Pb increased the protein amount of Zn-thionein in the liver of rats.…”
Section: )mentioning
confidence: 99%